ANALISIS SELF AFFECACY SEBAGAI INTERVENING, PENGETAHUAN BERWIRAUSAHA DAN TEKNOLOGI INFORMASI TERHADAP MINAT BERWIRAUSAHA MAHASISWA FEB UNTAG SEMARANG - Ilvan Sarif (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2022)
This research aims to determine the influence of knowledge of entrepreneurship, information technology and self-affecacy on the interest in entrepreneurship in students of the Faculty of Economics and Business, University of August 17, 1945 Semarang. The population in this study was 339 students of the Faculty of Economics and Business, University of 17 August 1945 Semarang. The sample size is 80 students with sampling techniques using proportionate ramdom sampling. Analaisis technique uses multiple regression findings from this study firstly entrepreneurial knowledge, information technology and self-affecacy have a positive and significant effect on the interest in entrepreneurship and secondly entrepreneurial knowledge, information technology has a positive and significant effect on self-affecacy.